Uji Beban Timbunan yang Diperkuat dengan Sistem Pelat Terpaku pada Tanah Gambut - Waruwu, Aazokhi; Hardiyatmo, Hary Christady; Rifa’i, Ahmad (Department of Civil Engineering, Diponegoro University, 2019)
One of the problems with peat soils, when subjected to imposed loads of construction, is the very high compression and long-term excessive settlement. The embankment can be built on peat soil, but it needs reinforcement that can contribute to increasing the stability of the embankment. The nailed slab system, as reinforcement, is expected to reduce settlement and increase the stability of peat soil. The aim of this paper is to study the effect of pile length and distance on the reduction of settlement in both monolithic and non-monolithic piles. The embankment load test was conducted on 70 cm x 120 cm plates, which were reinforced pile with different lengths and distances in the peat soil layer. The analysis was conducted on the reduction settlement of monolithic and non-monolith pile. The results showed that the length and distance of the pile had an effect on the reduction settlement. Changes in pile length are more dominant reducing settlement compared to changes in pile distance. Pile connection with slab has a significant effect on different lengths of piles than different distances piles.